Reconstruction of the late Holocene climate variability from the summer monsoon dominated Bhagirathi valley, western Himalaya. (15th April 2022) - Roy, Ipsita; Ranhotra, Parminder Singh; Tomar, Nidhi; Shekhar, Mayank; Agrawal, Shailesh; Bhattacharyya, Amalava; Kumar, Pankaj; Patil, Shiva Kumar; Sharma, Rajveer
Graphical abstract: Highlights: High resolution proxy data traced late Holocene climate events for western Himalaya. Sites have traced dry (4.2 ka; Little Ice Age) phases and moist Medieval warm period. Dry (weak summer monsoon) phases correspond well with decreased solar irradiance. Traced dry events are more prominent in drier alpine site than moist temperate site. LIA phase recorded asynchronous response time in Alpine and Temperate pollen data. Abstract: This study presents a centennial to decadal scale late Holocene climate scenario from the Indian summer monsoon (ISM) dominated region of western Himalaya. The subsurface sediments analyzed for palynology, carbon isotope (δ 13 Corg ) and magnetic susceptibility (χlf) were collected from the temperate and alpine meadows, respectively receiving high (low) and relatively low (high) amount of ISM (winter) precipitation. We could identify the dry and moist phases linked to respective weakening and strengthening of ISM. High frequency of steppe pollen ( Ephedra, Amaranthaceae, Asteraceae, Brassicaceae) between 4.4 and 3.8 ka represented a dry phase, coeval to 4.2 ka global dry event. Subsequent low δ 13 C values and high pollen frequency of moist vegetation (Geraniaceae, Cyperaceae, Apiaceae, Ranunculaceae and pteridophytes) till ca. 0.9 ka suggested moist phase but with an intermittent dry episode ca. 2.9–2.5 ka, allowing rise of steppe taxa. Climate ameliorated ca. 1.8 ka and moist conditions further enhanced between 1.5 and 0.9 ka, corresponding to Medieval Warm Period. Sharp increase in δ 13 Corg values and steppe vegetation ca. 0.8 ka attributed to dryness that intensified between 0.6 and 0.2 ka and coincide with Little Ice Age (LIA) anomaly. The recorded dry (weak ISM) phases showed correspondence with the low solar irradiance and supported the teleconnection with north Atlantic circulations. Palynological data from both the valleys complement each other throughout late Holocene time. However, the valleys showed temporal inconsistency in their aridity peaks during LIA phase. This indicates response variability of the two physiographically different sites to summer and winter monsoon systems.